Analisis Keterampilan Berpikir Kritis Siswa dengan Model Pembelajaran Problem Based Learning - Cahyati, Reni Agustina Eka; Ani, Hety Mustika; Herlindawati, Dwi (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to analyze critical thinking skills in problem-based learning. The research method used is quantitative descriptive research. The research sample was class XI Accounting 2. The sampling technique used purposive sampling. Data collection techniques using observation, tests, interviews, and document. The collected data were analyzed using descriptive techniques with percentages. Based on the results of the research that has been done, the results obtained that the critical thinking skills of students in class XI Accounting 2 SMK Muhammadiyah 1 Genteng in Accounting subjects general ledger material of 81.5% are in the “high” category.. This can be seen through the following indicators, interpretation ability of 85% is included in the "high" category, analysis ability of 84% is included in the "high" category, evaluation ability of 80% in the “high” category, inference ability of 77% in the "sufficient category".